Altered sensitivity to ethylene in 'Tardivo', a late‐ripening mutant of Clementine mandarin. Issue 4 (29th December 2013) - Alós, Enriqueta; Distefano, Gaetano; Rodrigo, María Jesús; Gentile, Alessandra; Zacarías, Lorenzo
<x xml:space="preserve">Abstract</x> 'Tardivo' mandarin is a mutant of 'Comune' Clementine with a delay in peel degreening and coloration, allowing late harvesting. In this work, we have explored if the late‐harvesting phenotype of 'Tardivo' mandarin is related to altered perception and sensitivity to ethylene. The peel degreening rate was examined after a single ethephon treatment or during a continuous ethylene application in fruits at two maturation stages. In general, ethylene‐induced peel degreening was considerably delayed and reduced in fruits of 'Tardivo', as well as the concomitant reduction of chlorophyll (Chl) and chloroplastic carotenoids, and the accumulation of chromoplastic carotenoids. Analysis of the expression of genes involved in Chl degradation, carotenoids, ABA, phenylpropanoids and ethylene biosynthesis revealed an impairment in the stimulation of most genes by ethylene in the peel of 'Tardivo' fruits with respect to 'Comune', especially after 5 days of ethylene application. Moreover, ethylene‐induced expression of two ethylene receptor genes, ETR1 and ETR2, was also reduced in mutant fruits. Expression levels of two ethylene‐responsive factors, ERF1 and ERF2, which were repressed by ethylene, were also impaired to a different extent, in fruits of both genotypes. Collectively, results suggested an altered sensitivity of the peel of 'Tardivo' to ethylene‐induced physiological and molecular responses, including fruit degreening and coloration processes, which may be time‐dependent since an early moderated reduction in the responses was followed by the latter inability to sustain ethylene action. These results support the involvement of ethylene in the regulation of at least some aspects of peel maturation in the non‐climacteric citrus fruit.